Role of CD147 in the development and diagnosis of hepatocellular carcinoma - Huang, Defa; Rao, Dingyu; Jin, Qing; Lai, Mi; Zhang, Jiali; Lai, Zhonghong; Shen, Haibin; Zhong, Tianyu (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC) is the most common primary liver cancer, and the third leading cause of cancer-related deaths worldwide. HCC is characterized by insidious onset, and most patients are diagnosed at an advanced stage with a poor prognosis. Identification of biomarkers for HCC onset and progression is imperative to development of effective diagnostic and therapeutic strategies. CD147 is a glycoprotein that is involved in tumor cell invasion, metastasis and angiogenesis through multiple mechanisms. In this review, we describe the molecular structure of CD147 and its role in regulating HCC invasion, metastasis and angiogenesis. We highlight its potential as a diagnostic and therapeutic target for HCC.